Australia’s fixed broadband deficit: Indecision around industry structure could entrench Australia’s laggard broadband position - McLaren, Gary (Journal of Telecommunications and the Digital Economy, 2020)
Australia’s fixed broadband services performance and takeup is continuing to fall behind other comparable countries in international benchmarks. This is despite broadband being a hot topic of debate at three Federal Elections and the creation of a new broadband utility company by the Australian Government. The recent change of government, in 2013, prompted reviews into the structure of Australia’s fixed telecommunications market. A move away from utility style broadband to infrastructure competition has been recommended but the Australian Government has not embraced such a move, preferring instead to keep the utility structure for fixed broadband. While the new Coalition Government is investing in more fibre infrastructure as part of its Multi Technology Mix, there is no commitment to build a ‘deep fibre’ network that would have ‘natural monopoly’ characteristics. Competition from new technologies, wireless and fixed, may limit the financial viability of the utility broadband provider. Indecision about the structure of Australia’s broadband market is likely to continue to retard medium to long term investment in the fibre infrastructure needed to improve Australia’s broadband rankings against its international peers.